2009
DOI: 10.1289/ehp.0900541
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Effects of Controlled Fine Particulate Exposure in Young Healthy Adults: Effect Modification by Ozone

Abstract: Background Human controlled-exposure studies have assessed the impact of ambient fine particulate matter on cardiac autonomic function measured by heart rate variability (HRV), but whether these effects are modified by concomitant ozone exposure remains unknown. Objective In this study we assessed the impact of O 3 and particulate matter exposure on HRV in humans. Methods In a crossover design, 50 subjects (19–48 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 38 publications
4
49
0
1
Order By: Relevance
“…Controlled-exposure studies have shown altered HRV after combined exposure to particles and ozone. 29,30 We also observed an increase in the duration of the QT interval immediately after exposure. A prolonged QT interval is a risk factor for ventricular tachyarrhythmias and sudden death.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Controlled-exposure studies have shown altered HRV after combined exposure to particles and ozone. 29,30 We also observed an increase in the duration of the QT interval immediately after exposure. A prolonged QT interval is a risk factor for ventricular tachyarrhythmias and sudden death.…”
Section: Discussionmentioning
confidence: 50%
“…We observed a decrease in the HF component of HRV immediately after ozone exposure, which is consistent with findings in multiple PM studies (PM Integrated Science Assessment). A previous controlled-exposure study 29 did not find significant ozone-induced changes in HRV. However, in this study, the participants were exposed to a smaller concentration of ozone (0.12 ppm) and did not exercise during exposure, which would have resulted in a smaller dose of ozone delivered to their airways.…”
Section: Discussionmentioning
confidence: 56%
“…Despite experimental support for cardiovascular effects of ozone (such as vascular oxidative stress and/or inflammation, increased heart rate, increased diastolic pressure, decreased heart rate variability and decreased nitric oxide bioavailability, for 2-hour to multi-day exposures to 500-800 ppb ozone) from animal models (Chuang et al, 2009;Perepu et al, 2010;Tankersley et al, 2010), results from controlled human studies remain ambiguous (Kusha et al, 2012;Fakhri et al, 2009). Similarly, investigation of blood biomarkers (reflecting haemostasis and inflammation) of cardiovascular risk in panel studies have provided inconsistent associations with ozone, complicated by the different averaging times and lag structures examined (Rudez et al, 2009;Thompson et al, 2010;Chuang et al, 2007;Liao et al, 2005;Steinvil et al 2008).…”
Section: Experimental and Panel Studiesmentioning
confidence: 99%
“…This may be associated with the biomarker changes observed by the authors, because other studies using ozone exposure regimens that likely produced a lower pulmonary response have not reported changes in heart rate variability. 4 Finally, Devlin et al suggest that their findings provide support for cardiovascular effects reported in some epidemiology studies. Exposures in epidemiology studies are generally an order of magnitude lower and the effects far more extreme (eg, death).…”
mentioning
confidence: 80%